Analisa pengaruh atmosfer toko terhadap perilaku belanja konsumen pada gerai Farmers Market area Jakarta Utara - Hardiyanti, Putri (Universitas Tarumanagara, 2017)
This research aimed to know the influence of store atmosphere on customer behavior at Farmers Market’s outlets in the North Jakarta Area. The data collection method is done by spreading the questionnaire to measure consumer behavior response to store atmosphere variables. The number of samples taken in this study is 135 respondents who have been to Farmers Market’s outlet in Baywalk Mall and Mall Kelapa Gading in the last 6 months. The data analysis technique of the research was qualitative analysis and using a simple linear regression method. The R-Square for this research model indicates that all store atmosphere factors have simultaneous correlations with customer behavior. Partial test results (t-test) showed that the store atmosphere variable (with ambiance, space, and function sub-variables, as well as signs, symbols, and artifacts sub-variables) had positive influences on the customer behavior variable. A very interesting finding from this research indicates that store atmospheric factors have a positive correlation with customer behaviors.